PENGARUH AUDIT PARTNER TENURE, ROTASI KAP, DAN UKURAN KAP TERHADAP KUALITAS AUDIT - Atina Nur Aulia; Daljono Daljono (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of audit partner tenure, audit firm rotation, and audit firm size on audit quality. Some of the variables that used in this study are audit quality which uses discretionary accruals as dependent variable, audit partner tenure, audit firm rotation, and audit firm size as independent variables, also firm loss, leverage, and firm size as control variables. The sample that used in this study were companies from manufacturing sector that listed on the Indonesia Stock Exchange during 2017-2019. The sample was selected using purposive sampling technique based on several criteria, so that the sample at the end of the study were 307 companies. The method that used to test the hypothesis is multiple linear regression analysis. The results from the hypothesis testing show that audit partner tenure has a negative and significant effect on audit quality. Likewise, audit firm rotation shows the same result, which has a negative and significant effect on audit quality. Meanwhile, audit firm size does not show a significant effect on audit quality.